Captive-reared migratory monarch butterflies show natural orientation when released in the wild. Issue 1 (11th May 2021) - Wilcox, Alana A E; Newman, Amy E M; Raine, Nigel E; Mitchell, Greg W; Norris, D Ryan
Abstract : Recent work suggests captive-reared monarch butterflies lose their capacity to fly southward in fall, questioning the value of captive rearing. We show that, in contrast to captive-reared monarchs flown in a flight simulator, monarchs reared under laboratory conditions and released in the wild showed proper southward orientation. Abstract: Eastern North American migratory monarch butterflies ( Danaus plexippus ) have faced sharp declines over the past two decades. Captive rearing of monarch butterflies is a popular and widely used approach for both public education and conservation. However, recent evidence suggests that captive-reared monarchs may lose their capacity to orient southward during fall migration to their Mexican overwintering sites, raising questions about the value and ethics of this activity undertaken by tens of thousands of North American citizens, educators, volunteers and conservationists each year. We raised offspring of wild-caught monarchs on swamp milkweed ( Asclepias incarnata ) indoors at 29°C during the day and 23°C at night ( 77% RH, 18L:6D), and after eclosion, individuals were either tested in a flight simulator or radio tracked in the wild using an array of automated telemetry towers. While 26% (10/39) of monarchs tested in the flight simulator showed a weakly concentrated southward orientation, 97% (28/29) of the radio-tracked individuals that could be reliably detected by automated towers flew in a south to southeast direction from the release site and were detected at distances of up to 200 km away. Our results suggest that, although captive rearing of monarch butterflies may cause temporary disorientation, proper orientation is likely established after exposure to natural skylight cues.